Nantucket red tickets : a Henry Kennis mystery - Axelrod, Steven (Axelrod, Steven. Henry Kennis mystery., 2016)
It's Christmas Eve on Nantucket and prominent businessman Jackson Blum is about to live out his own version of A Christmas Carol.